Dimensi religiositas dalam Kandan Dayak Siang - Poerwadi, Petrus; Yusnia, Yusnia (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to describe the dimensions of religiosity contained in Kandan Nawui Bojah. These dimensions of religiosity include (1) the ideology/belief dimension, (2) the practice dimension of worship, (3) the experience dimension, (4) the dimension of religious knowledge, and (5) the consequence dimension contained. In Kandan Nawui Bojah/Beas, there is an ideological dimension in the form of a view that acknowledges the truth that through the sown rice, they can communicate and convey messages to their sangiang or ancestors. The dimensions of worship practices in Kandan Nawui Bojah can be seen in the rituals carried out by the Dayak Siang community. They practice worship by sowing rice (bojah tawui). The Experience Dimension in Kandan Bojah Nawui is seen in the experience or perception that padi or rice has long been promised to humans that it will support humans. The dimension of religious knowledge in Kandan can be seen in knowledge about the ritual of nawui bojah or sowing rice. Community religious knowledge regarding the ritual of nawui bojah, or sowing rice, is absolute and must be believed by Kaharingan followers. The consequence dimension contained in Nawui Bojah's kandan explains the consequences that occur if someone wastes rice.